Stereocontrolled Photodimerization of (E)-3-Benzylidene-4-chromanones in the Crystalline State: The Effect of a Halogen Group on the Chromanone Moiety - Cheng, Xue-Ming; Chen, Min; Huang, Zhi-Tang; Zheng, Qi-Yu (Synthesis, 2012)
A series of (E)-3-benzylidene-4-chromanone derivatives are synthesized, which are substituted with a halogen group on the chromanone moiety in order to control the molecular arrangement in the crystalline state. The stereoselective photoreactions of these compounds in the solid state are examined based on the crystal structures of the reactants and products. All the examples tested undergo photodimerization, except for (E)-3-benzylidene-6-fluorochroman-4-one. The reactants with β-structures give syn-head-to-head (syn-HH) products with high selectivity. Only (E)-6-chloro-3-(4-methylbenzylidene)-chroman-4-one adopted the α-form and gives an anti-head-to-tail (anti-HT) product.
Keywords: photodimerization; alkenes; photochemistry; chromanones; halogens